Kompetensi, Pengalaman, dan Pembelajaran Inovasi yang Memengaruhi Kemampuan Berinovasi dan Sukses Kewirausahaan - Djojo, Brata Wibawa (Binus Business Review, 2013)
Entreprneurship is one of economic indicator in a country, whereas the entrepreneur would make a job impact to many people. Entrepreneurship could not be implemented without the willingness and capability to make effort.Â  An entrepreneur must have a vision of business opportunities as well, especially in health industry in Indonesia in forthcoming days. The question is on how an entrepreneur could success in health business relating to his or her competencies, experiences, and innovation learning in which also affect innovation capability. This paper studies about some successful Indonesian entrepreneurs in health business whom make an inspiration and input to entrepreneur candidates or existing entrepreneurs. This paper is supported by theoretical review to find the research modelâs variables for future research, which might be in empirical study. This paper used judgement sampling method to Indonesian entrepreneurs in health business. The interesting issue is that the competency and success of the entrepreneurs do not always relate to formal education they got, but how the entrepreneurs implement the innovation way in their business. There are some gaps in this paper, whereas how the similiar research could take a good sample and exploit the research design well in the future to get a good and accurate research.